Transformation of Surau as an Islamic Educational Institution in Minangkabau: A Case Study of Surau Cubadak Palayangan: Transformasi Surau Sebagai Lembaga Pendidikan Islam Di Minangkabau: Studi Kasus Surau Cubadak Palayangan - Desfitri Anggi; Ayu Citra Dewi; Diana Sartika (Ikhtisar: Jurnal Pengetahuan Islam, 2025)
This study aims to describe the transformation of Surau Cubadak Palayangan as an educational institution for Islamic values in Korong Palayangan, Nagari Balah Hilia, Lubuk Alung District, Padang Pariaman Regency. Initially functioning as a place of worship and tarekat (Sufi order) activities, the surau has undergone a significant transformation into a non-formal Islamic educational institution that plays an important role in the moral, spiritual, and social development of the community. This research employs a qualitative approach with a descriptive method to deeply understand the social phenomena, values, and meanings embedded in the role of the surau within Minangkabau society. Data were collected through direct observation, in-depth interviews with religious figures, surau administrators, and community members, as well as documentation of various religious activities held in the surau. The findings reveal that the transformation of Surau Cubadak Palayangan occurred through changes in its learning system and the expansion of its function into a structured Islamic educational center. The surau applies both traditional and contextual teaching methods, such as lectures (ceramah), halaqah (study circles), talaqqi-takrir (repetition learning), storytelling (qashash), role modeling (uswah hasanah), and the habituation of Islamic values. This transformation demonstrates that the surau remains highly relevant in shaping the character, morality, and Islamic identity of Minangkabau society, serving as a symbol of integration between religion, education, and culture that endures amidst modern societal changes..